# Test 12-16

 Page 1 / 1

## Without templates

Theorem 1: a n x n + ... + a 1 x + a 0   is   O ( x n )   for any real numbers a n , ..., a 0 and any nonnegative number n .

## With templates

an xn + ... + a1 x + a0   is   O( xn )   for any real numbers an , ..., a0 and any nonnegative number n .

## Without templates

Theorem 1: calling makeLayer with valid inputs (a list of weights and two non-zero natural numbers) returns a valid layer recognized by isLayer. (“layers.lisp”)

Theorem 2: calling makeNetwork with valid inputs (a list of non-zero natural numbers and a list of weights) returns a valid network recognized by isNetwork. (“networks.lisp”)

## With templates

calling makeLayer with valid inputs (a list of weights and two non-zero natural numbers) returns a valid layer recognized by isLayer. (“layers.lisp”)

calling makeNetwork with valid inputs (a list of non-zero natural numbers and a list of weights) returns a valid network recognized by isNetwork. (“networks.lisp”)

## Without templates

Theorem 4: a n x n + ... + a 1 x + a 0   is   θ ( x n )   for any real numbers a n , ..., a 0 and any nonnegative number n .

Let f ( x ) and g ( x ) be functions from a set of real numbers to a set of real numbers.

Then

1.     If   $f\left(x\right)/g\left(x\right)=0$ , then   f ( x ) is  o ( g ( x ) ) . Note that if   f ( x ) is  o ( g ( x ) ), then  f ( x ) is  O ( g ( x ) ).

2.     If  $f\left(x\right)/g\left(x\right)=\infty$ , then   g ( x ) is o ( f ( x ) ) .

3.     If   $f\left(x\right)/g\left(x\right)<\infty$ , then   f ( x ) is θ ( g ( x ) ) .

4.     If   $f\left(x\right)/g\left(x\right)<\infty$ , then   f ( x ) is O ( g ( x ) ) .

For example,

 (4x 3 + 3x 2 + 5)/(x 4 – 3x 3 – 5x -4)

=  ( 4/x + 3/x 2 + 5/x 4 )/( 1 - 3/x - 5/x 3 - 4/x 4 ) = 0 .

Hence

( 4x 3 + 3x 2 + 5 )   is   o ( x 4 - 3x 3 - 5x - 4 ),

or equivalently,   ( x 4 - 3x 3 - 5x - 4 ) is   ω ( 4x 3 + 3x 2 + 5 ) .

Let us see why these rules hold. Here we give a proof for 4. Others can be proven similarly.

Proof : Suppose   $f\left(x\right)/g\left(x\right){\text{=C}}_{1}<\infty$ .

By the definition of limit this means that

∀ε>0, ∃ n 0 such that   | f(x)/g(x) C 1 |<ε whenever x> n 0

Hence –ε < f(x)/g(x) C 1

Hence –ε + C 1 < f(x)/g(x) <ε + C 1

In particular f(x)/g(x) <ε + C 1

Hence f(x) <(ε + C 1 ) g(x)

Let C = ε + C 1 , then f(x) < Cg(x) whenever x> n 0 .

Since we are interested in non-negative functions f and g , this means that   | f ( x ) | C | g ( x ) |

Hence   f ( x ) = O ( g ( x ) ) .

## With templates

an xn + ... + a1 x + a0   is   θ( xn )   for any real numbers an , ..., a0 and any nonnegative number n .

Let f(x) and g(x) be functions from a set of real numbers to a set of real numbers.

Then

1.     If   $f\left(x\right)/g\left(x\right)=0$ , then  f(x) is o( g(x) ) . Note that if  f(x) is o( g(x) ), then f(x) is O( g(x) ).

2.     If  $f\left(x\right)/g\left(x\right)=\infty$ , then   g(x) is o( f(x) ) .

3.     If   $f\left(x\right)/g\left(x\right)<\infty$ , then   f(x) is θ( g(x) ) .

4.     If   $f\left(x\right)/g\left(x\right)<\infty$ , then   f(x) is O( g(x) ) .

For example,

 (4x3 + 3x2 + 5)/(x4 – 3x3 – 5x -4)

=  ( 4/x + 3/x2 + 5/x4 )/(1 - 3/x - 5/x3 - 4/x4 ) = 0 .

Hence

( 4x3 + 3x2 + 5 )   is   o(x4 - 3x3 - 5x - 4 ),

or equivalently,   (x4 - 3x3 - 5x - 4 ) is   ω(4x3 + 3x2 + 5 ) .

Let us see why these rules hold. Here we give a proof for 4. Others can be proven similarly.

Proof: Suppose   $f\left(x\right)/g\left(x\right){\text{=C}}_{1}<\infty$ .

By the definition of limit this means that

∀ε>0, ∃n0 such that   |f(x)/g(x) – C1|<ε whenever x>n0

Hence –ε<f(x)/g(x) – C1<ε

Hence –ε +C1<f(x)/g(x)<ε +C1

In particular f(x)/g(x)<ε +C1

Hence f(x)<(ε +C1)g(x)

Let C = ε +C1 , then f(x)<Cg(x) whenever x>n0 .

Since we are interested in non-negative functions f and g, this means that   |f(x) | ≤C | g(x) |

Hence   f(x) = O( g(x) ) .

test

show that the set of all natural number form semi group under the composition of addition
what is the meaning
Dominic
explain and give four Example hyperbolic function
_3_2_1
felecia
⅗ ⅔½
felecia
_½+⅔-¾
felecia
The denominator of a certain fraction is 9 more than the numerator. If 6 is added to both terms of the fraction, the value of the fraction becomes 2/3. Find the original fraction. 2. The sum of the least and greatest of 3 consecutive integers is 60. What are the valu
1. x + 6 2 -------------- = _ x + 9 + 6 3 x + 6 3 ----------- x -- (cross multiply) x + 15 2 3(x + 6) = 2(x + 15) 3x + 18 = 2x + 30 (-2x from both) x + 18 = 30 (-18 from both) x = 12 Test: 12 + 6 18 2 -------------- = --- = --- 12 + 9 + 6 27 3
Pawel
2. (x) + (x + 2) = 60 2x + 2 = 60 2x = 58 x = 29 29, 30, & 31
Pawel
ok
Ifeanyi
on number 2 question How did you got 2x +2
Ifeanyi
combine like terms. x + x + 2 is same as 2x + 2
Pawel
x*x=2
felecia
2+2x=
felecia
×/×+9+6/1
Debbie
Q2 x+(x+2)+(x+4)=60 3x+6=60 3x+6-6=60-6 3x=54 3x/3=54/3 x=18 :. The numbers are 18,20 and 22
Naagmenkoma
Mark and Don are planning to sell each of their marble collections at a garage sale. If Don has 1 more than 3 times the number of marbles Mark has, how many does each boy have to sell if the total number of marbles is 113?
Mark = x,. Don = 3x + 1 x + 3x + 1 = 113 4x = 112, x = 28 Mark = 28, Don = 85, 28 + 85 = 113
Pawel
how do I set up the problem?
what is a solution set?
Harshika
find the subring of gaussian integers?
Rofiqul
hello, I am happy to help!
Abdullahi
hi mam
Mark
find the value of 2x=32
divide by 2 on each side of the equal sign to solve for x
corri
X=16
Michael
Want to review on complex number 1.What are complex number 2.How to solve complex number problems.
Beyan
yes i wantt to review
Mark
16
Makan
x=16
Makan
use the y -intercept and slope to sketch the graph of the equation y=6x
how do we prove the quadratic formular
Darius
hello, if you have a question about Algebra 2. I may be able to help. I am an Algebra 2 Teacher
thank you help me with how to prove the quadratic equation
Seidu
may God blessed u for that. Please I want u to help me in sets.
Opoku
what is math number
4
Trista
x-2y+3z=-3 2x-y+z=7 -x+3y-z=6
can you teacch how to solve that🙏
Mark
Solve for the first variable in one of the equations, then substitute the result into the other equation. Point For: (6111,4111,−411)(6111,4111,-411) Equation Form: x=6111,y=4111,z=−411x=6111,y=4111,z=-411
Brenna
(61/11,41/11,−4/11)
Brenna
x=61/11 y=41/11 z=−4/11 x=61/11 y=41/11 z=-4/11
Brenna
Need help solving this problem (2/7)^-2
x+2y-z=7
Sidiki
what is the coefficient of -4×
-1
Shedrak
Got questions? Join the online conversation and get instant answers!